Cytotoxicity of crude proanthocyanidin extract from purple glutinous rice bran (Oryza sativa L.) (Kum Doi Saket) compared with cyanidin 3-glucoside on X63 myeloma cancer cell lines - Punyatong M. (2014)
Proanthocyanidin and other phenolic compounds may potentially reduce the risk of cardiovascular diseases and cancer, as well as having antioxidant, anti-inflammatory and chemoprotective properties. Proanthocyanidin (PA) and cyanidin 3-glucoside (C3G), a polyphenolic compound of purple color found in purple glutinous rice (Oryza sativa L.), may also manifest these positive effects. This research evaluated the effect of PA and C3G on X63, a mouse-plasma cancer cell line of myeloma cells. PA and C3G were extracted from the purple rice bran of a local, Thailand, purple, rice genotype (Kum Doi Saket). The results showed that the amount of C3G extract from the rice genotype was 54.47 mg/100 g rice bran. The cytotoxicity of the crude PA extract was demonstrated by a dose-dependent decrease in the percentage cell viability of the control in the PA group. A significant difference (p<0.05) began at 100 μg/ml and IC50 occurred at 62.29 μg/ml. The C3G extract also exhibited a dose-dependent decrease, but the significant difference (p<0.05) began at 10 μM and IC50 occurred at 8.4 μM. This research demonstrated a dose-related cytotoxic effect on cancer cells by the crude PA and C3G extracts from purple glutinous rice. The results indicated the benefit of the purple rice genotypes as a functional food with potential anticancer properties.